2003
DOI: 10.1016/s1472-6483(10)62059-7
|View full text |Cite
|
Sign up to set email alerts
|

Counselling lesbian couples: requests for donor insemination on social grounds

Abstract: Fertility centres are increasingly involved in dealing with requests from lesbian couples for donor insemination (DI). Data were collected on 95 Belgian lesbian couples who applied for DI. The majority of couples were well integrated in a social environment (family, friends and work) that consisted mainly of heterosexuals. They tended to be open about their homosexuality and most couples considered the social environment to be tolerant towards their homosexual orientation. Couples who considered alternatives t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 28 publications
3
9
0
4
Order By: Relevance
“…Consistent with the research of Herrmann-Green and Gehring (2007) and Baetens (2002), the results from this study suggest that internalized stigma of sexual minority members is generally low. In this study no significant differences between mothers and childless women were found, unlike the findings of the study by DeMino and colleagues (2007).…”
Section: Limitationssupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with the research of Herrmann-Green and Gehring (2007) and Baetens (2002), the results from this study suggest that internalized stigma of sexual minority members is generally low. In this study no significant differences between mothers and childless women were found, unlike the findings of the study by DeMino and colleagues (2007).…”
Section: Limitationssupporting
confidence: 91%
“…Lesbian mothers and their partners have to contend with coming out publicly in most social contexts. Although studies show that these women generally exhibit low levels of internalized homophobia (i.e., internalized stigma as a result of sexual orientation) (Baetens, 2002;HerrmannGreen & Gehring, 2007), a comparative study involving lesbian mothers and childless lesbian women found that mothers nonetheless scored higher with regard to internalized homophobia compared to those who were childless. Despite receiving more support from their family of origin, these mothers received less social support from their heterosexual and nonheterosexual friends (DeMino, Appleby, & Fisk, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, the proportion of lesbians who choose to parent and have a previous history of depression is unknown. Since some clinics will not inseminate a woman (lesbian or heterosexual) who meets criteria for a psychiatric disorder at the time of the insemination request (Baetens, Camus, & Devroey, 2002), rates of major depression in lesbians undergoing medically-assisted donor insemination may be lower than rates in the total population of lesbian and bisexual women.…”
Section: Mental Health Historymentioning
confidence: 99%
“…About half of the couples regarded themselves as a two‐mother unit, the remaining couples as one mother and one other parent (11). In English‐speaking countries, the child in nine out of 10 families called the respective parents mommy/mama or mommy‐first‐name.…”
Section: Resultsmentioning
confidence: 99%